Synthesis and electrochemical performance of nickel-based electrodes for supercapacitor applications - Korkmaz, Caner; Coban, Berk; Zaman, Buse Tugba; Bakirdere, Sezgin; Gencten, Metin (SPRINGER, 2025)
In this study, the electrochemical performance of nickel oxide-based magnetic nanoparticles (NiOMNP) and nanoflower-shaped Ni(OH)2 were used as electrodes, and was investigated for supercapacitor applications. Galvanostatic charge-discharge (GCD) measurements demonstrated that both electrodes exhibited excellent cycling stability with NiOMNP retaining 96.43% of its initial capacitance after 15,000 cycles, while Ni(OH)2 showed an increase in capacitance to 129.16% due to a self-activation process. The superior long-term stability of NiOMNP was attributed to its structural robustness, whereas the capacitance enhancement in Ni(OH)2 was linked to improved electrolyte-electrode interaction over time. The areal capacitance values of NiOMNP and Ni(OH)2 reached 91 mF cm-2 and 74 mF cm-2, respectively at 10 mV s-1, demonstrating their high charge storage capability. Comparison with the literature data indicated that the electrodes synthesized in this study outperformed many previously reported NiOMNP and Ni(OH)2-based electrodes. These findings highlight the potential of Ni-based electrodes for high-performance supercapacitor applications.
Keywords: ENERGY-STORAGE; PSEUDOCAPACITANCE; DEPOSITION; IMPEDANCE; Engineering; Materials Science; Physics